Bridging Japanese/North American differences - Gudykunst, William B. (Communicating effectively in multicultural contexts, 1994)
After laying out the basic theories of intercultural communication, this book explains the similarities and differences in patterns of communication in Japan and the United States. The authors then demonstrate how an understanding of these contrasting patterns can help Japanese and North Americans communicate more effectively.